Status Regeneration in First John: Social Scientific and Literary Perspectives - Snodderly, B.; Merwe, Dirk G. van der (Acta Patristica et Byzantina, 2007)
A socio-rhetorical approach to analyzing portions of the text of First John brings out new answers to questions about the text, related to genre, structure and interpretation that have puzzled biblical commentators over the years. This article looks at the text from two perspectives. From a socio-rhetorical perspective it looks at the text through lens of a social-scientific model termed by Bruce Malina and Jerome Neyrey a “Status Degradation Ritual”2 (adapted from sociologist Harold Garfinkel3), which enriches the understanding of the purposes, genre and structure of First John. From a literary perspective this article looks at the way language is used to facilitate the Status Degradation Ritual and finds the intentional use of chiasm, a common oral-literary device in ancient Hebrew4 and Greco-Roman literature. Insights from the chiastic parallelisms of the structure of the proposed Status Degradation Ritual offer new explanations for exegetical issues such as the seeming contradiction between 1 John 1:8, 10 and 3:6, 9 regarding the sin and sinlessness of the believer.
free